Islamic Education as a Foundation for Religious Entrepreneurship in Islamic Higher Education Institutions - Herlinda; Musa Thahir; Annisaul Khairat (Ta'dib, 2025)
This study aims to examine the relationship between Islamic education and the development of religious entrepreneurial character among students at Islamic Higher Education Institutions in Riau Province, with particular attention to educational and institutional factors that support or constrain the implementation of sharia-based entrepreneurship education. Employing a quantitative cross-sectional survey design, data were collected from 76 PTKI students through a structured questionnaire and analyzed using descriptive and inferential statistical techniques with SPSS to identify dominant patterns and associative tendencies among the studied variables. The results indicate that experiential learning practices, institutional collaboration with industry, and the integration of digital technology are perceived as the most influential factors in strengthening religious entrepreneurial character. Conversely, limited sharia economic literacy, inadequate educational facilities, and restricted access to entrepreneurial resources emerge as key constraints, alongside external influences such as socio-cultural environments and market competition. From a practical perspective, the findings suggest that PTKI need to strengthen experiential learning opportunities, expand partnerships with sharia-based industries, and enhance technological and mentoring support to improve the effectiveness of Islamic entrepreneurship education. The novelty of this study lies in its empirical contextualization of religious entrepreneurship education within the PTKI environment in Riau, highlighting the persistent gap between normative Islamic entrepreneurial values and their pedagogical implementation. Rather than proposing or validating an instructional model, this study contributes by offering evidence-based insights that can inform curriculum refinement and institutional strategies aimed at fostering religious entrepreneurial character in Islamic higher education.